An ABC-analysis of Ethical Organizational Behavior - Nijhof, André H. J. (Journal of business ethics, 1999)
The Antecedent-Behavior-Consequence (ABC)-analysis is a tool for analyzing behavior and stems from the field of psychology where it is used as a tool for the understanding of behavior in general and organizational behavior in particular. In this paper the ABC-analysis is implemented as a tool to understand why people behave ethically in organizations, through the identification of key environmental factors that cause such behavior. This analysis can be the first step to recognizing the complexity of circumstances determining ethical behavior, as well as trigger for changing that behavior. This will be elaborated in the implementation process of an ethical code. The working of the ABC-analysis will be illustrated with an example derived from field research concerning the reorganization of a department of a chemical company.